Analysis of the Influence of Biology Teachers' Creativity on Motivation, Critical Thinking Ability and Student Learning Outcomes During a Pandemic Through Online Learning of the Concept of the Human Reproductive System in Class XI Students of SMA - Elsina B. Lasang; Johanis F, Rehena; I. Muhammad Nur Matdoan (Peneliti.net, 2021)
At this time the Covid-19 pandemic or known as the corona virus has been endemic in the world and has affected aspects of human life. To break the chain of transmission of the corona virus, the government has set various policies for the community, one of which is in the world of education. Social distancing and physical distancing policies to break the spread of the corona virus outbreak, forcing a change from formal education in school to learning from home using an online system on a national scale, this makes teachers required to be able to design the learning process creatively by using models, methods, and methods. media and learning strategies that are in accordance with the subject matter in order to stimulate motivation, critical thinking skills and student learning outcomes and make students less likely to feel bored in participating in the online learning process. This study aims to examine the effect of biology teacher creativity on online learning to improve motivation, critical thinking skills and learning outcomes of class XI MIPA students at SMA Angkasa Lanud Pattimura Ambon, SMAN 3 Ambon and SMAN 7 Ambon. The data of this study were analyzed using multiple regression test. Through this research, it can be said that the creativity of biology teachers in carrying out online learning of the concept of the human reproductive system in the midst of the covid-19 pandemic in class XI students of SMA Angkasa Lanud Pattimura, SMAN 3 Ambon and SMAN 7 Ambon has a significant effect on motivation, critical thinking skills and student learning outcomes